Juridical Analysis of The Authority of The District Court to Postpone Elections (Study of Decision Number 757/PDT.G/2022/PN JKT.PST) - Khofifah Kusumawardhani; Labib Muttaqin (Proceeding International Conference Restructuring and Transforming Law, 2024)
In early March 2023, Indonesia was shocked by the issue of postponing elections. A lawsuit was granted by the Central Jakarta District Court in decision number 757/Pdt.G/2022/PN Jkt.Pst to not conduct the remaining stages of the 2024 General Election filed by the Prima Party. This research uses doctrinal or normative methods including comparison, systematics, level of synchronization, history, and legal principles. The researcher uses the literature study method to obtain and collect data. Qualitative normative analysis and deductive reasoning techniques are used to analyze the data in this study. Article 2 paragraph (1) of Supreme Court Regulation 2/2019 clearly states that the State Administrative Court is responsible for cases of unlawful acts which are filed by government agencies and/or officials. It should not be the domain of the District Court to decide. The Central Jakarta District Court exceeded its authority by deciding a dispute with a government body in a case of unlawful act. The District Court does not have the absolute competence to decide cases such as those filed by the Prima Party in Decision Number 757/Pdt.G/2022/PN Jkt.Pst.